Effect of Dexamethasone Implant on Subfoveal Choroidal Thickness in Early Period in Vitrectomized Eyes with Diabetic Macular Edema - A. Altun; A. M. Hacimustafaoglu (Journal of Ophthalmology)
Aim. To investigate the change in subfoveal choroidal thickness (SFCT) in vitrectomized eyes with intravitreal dexamethasone (IVD) implant injection for the treatment of diabetic macular edema (DME). Method. In this prospective and controlled study, the vitrectomized eyes of diabetic patients were included. The study group (Group 1) was formed by diabetic vitrectomized eyes with DME. The control group (Group 2) was formed by diabetic vitrectomized eyes without DME. Only one intravitreal IVD implant was injected into the eyes in Group 1. In the first, second, and fourth months, choroidal layers were measured by optical coherence tomography and complete ophthalmologic examinations were performed for all cases. Results. Ninety-six eyes of 96 cases were included in the study. There were 48 eyes of 48 different patients in each group. After IVD injection, statistically significant improvement was observed in the best corrected visual acuity in Group 1. The mean SFCT in eyes with DME was statistically significantly thinner (p < 0.01) and thinness became more pronounced during the four-month follow-up period after IVD implant injection (p < 0.01). Conclusion. In the presence of DME in vitrectomized eyes, the thinness of the SFCT may become evident after dexamethasone implant injection.